Penoscrotal swelling—an unusual occurrence in a patient with an anastomotic leak following ileostomy closure. Issue 8 (6th August 2018) - Bojanapu, Srinivas; Nagar, Anand; Mehrotra, Siddharth; Mangla, Vivek; Lalwani, Shailendra; Yadav, Amitabh; Mehta, Naimish; Nundy, Samiran
Abstract: Diverting loop ileostomy is a frequently done procedure accompanying colorectal surgeries. Dreaded complication is anastomotic leak. Early identification of anastomotic leak and apt management is required for better outcomes. Most often leak presents with fever, abdominal pain, rigidity, fever and hemodynamic instability. We report a rare occurrence of penoscrotal oedema in a patient with anastomotic leak and spontaneously subsiding with drainage of leaked contents.